Creep buckling of high strength Q460 steel columns at elevated temperatures. (June 2019) - Wang, Weiyong; Zhou, Hongyang; Xu, Lei
Abstract: When it is subjected to a fire, creep strain developed in a steel column can significantly influence the behaviour of the column. As the result, the column deformation will be increased and the strength will be decreased. However, the effect of creep in steel structures has not been fully considered in current fire resistance design codes. Presented in this paper is a study on creep buckling of Q460 steel columns subjected to elevated temperatures via experimental and numerical investigations. Six high-strength Q460 steel columns with welded H shape were tested for the determination of creep buckling strength at elevated temperatures. The effects of the slenderness ratio, load ratio, and elevated temperature on failure time corresponding to creep buckling (also called as creep buckling time) were taken into consideration in the investigations. The evolutions of furnace and column temperatures, column lateral and axial displacements associated with fire duration were measured. The creep buckling time of the columns were obtained based on the magnitudes of axial and lateral displacement of the columns subjected to constant elevated temperature and compressive load. The test results showed that the creep deformation of high strength Q460 steel columns became significant at temperature 800 °C even the applied load level was as low as 10%. The creep buckling time of Q460 steel columns are sensitive to load ratio, slenderness and temperature. Finite element analysis program ANSYS was employed to establish a structural model of Q460 steel column subjected to the constant elevated temperature and compressive load, with mechanical properties at elevated temperature, creep strains and residual stresses induced by welding being taken into account. The finite element model was validated by the test results. Parametric studies were carried out to quantitatively determine the effects of the slenderness ratio, load ratio, temperature and geometric imperfections on the creep buckling time of Q460 steel columns. Highlights: Creep buckling tests on high strength Q460 steel columns at elevated temperature were presented. A finite element model was established to predict creep deformation and creep buckling time of Q460 steel columns. The effect of key parameters on creep buckling were investigated by test and finite element simulation.